(Dis)loyalty in the German dairy industry: a supplier relationship management view ; empirical evidence and management implications - Birgit Schulze; Christian Wocken; Achim Spiller (Georg-August-Universität Göttingen, Department für Agrarökonomie und Rurale Entwicklung (DARE), 2008)
During the last decades there have been many empirical and theoretical attempts to approach the question of how to build and maintain stable, long-term relationships (Hennig- Thurau and Hansen, 2000; Andaleeb, 1996). In neoclassical analysis, one would typically argue that the decision to whom to deliver one's products or from whom to buy them is only based on price. The perception that the homo oeconomicus is no appropriate idea of man for the analysis of enduring business relationships, however, is not new (Heide, 1994). Today, it is widely accepted that behavioural aspects such as commitment and loyalty also play an important role in economic exchanges.
Keywords: 330